The Legal Basics of the International Cooperation of Russia in the Field of Telecommunications - A. V. Kolesnikova (Московский журнал международного права, 2012)
International cooperation of Russia in the field of production, technology, telecommunications – is an instrument of the modernization of the science sectors of the economy of the country, a catalyst of the scientific and technological advances in the field of the communications, information and communication infrastructure. International Telecommunication Union is the United Nations specialized agency for information and communication technologies. The article is devoted to the legal basics of the international cooperation of Russia in the field of telecommunications; investigates the state of the international telecommunications regime and studies the basic acts in the area of the telecommunications; to the description of the activity of the Regional Commonwealth in the field of communications, having been covering a different aspects of the info telecommunications’ industry in the Commonwealth of Independent States.